Finance data mining1 - Anh Cuong, Tran (2012)
The author uses quantitative media data generated by large-scale natural language processing (NLP) text analysis systems to perform a comprehensive and comparative study on how a Twitter mood reflects its stock trading volumes. The resources for analyzing are user profile and tweets information which were collected from Twitter. Even the general results for a period of 1 year are not high (10.4%), however in some specific periods such as June 2011 or from 11th September to 21st October 2011, the accuracy outcome are about 34% and 40% respectively. This is the concrete evidence to show that media data is highly informative.